Staphylococcus sciuri causes disease and pathological changes in hybrid sturgeon acipenser baerii × acipenser schrencki - Zhang, Mengwei; Xue, Mingyang; Xiao, Zidong; Liu, Wei; Jiang, Nan; Meng, Yan; Fan, Yuding; Liu, Xiaoling; Zhou, Yong (Frontiers in Cellular and Infection Microbiology, 2022)
Hybrid sturgeon is the main species of sturgeon cultured in China, with the advantages of a fast growth rate, early sexual maturity, fertile offspring, and more stable genetic traits. In May 2021, a large number of deaths characterized by superficial hemorrhage and liver damage occurred in a sturgeon farm in Yichang, Hubei Province, which posed a significant risk to hybrid sturgeon captive breeding. We isolated a pathogenic bacterium named D-59 from the diseased sturgeon with apparent symptoms. The pathogen was identified as Staphylococcus sciuri using 16S rRNA gene phylogenetic analysis combined with biochemical identification. Regression experiments showed that D-59 exhibited clinical signs similar to those of diseased sturgeon in the farm after intraperitoneal injection into hybrid sturgeon. High-throughput sequencing of gut microbes in D-59-infected sturgeon showed that the number of gut microbial species decreased in infected sturgeon, the number of some intestinal commensal bacteria decreased, and the balance of the intestinal microorganisms was disrupted. Histopathological sections indicated many inflammatory cells, congestion, and even necrosis in the tissue of diseased sturgeon. Analysis of blood indexes revealed an increase in the proportion of mononuclear cells and a decrease in the proportion of lymphocytes in the peripheral blood of diseased sturgeon. Significantly elevated serum levels of aspartate aminotransferase and alanine aminotransferase, whereas alkaline phosphatase, total protein, albumin, and globulin were decreased in diseased sturgeon. Antimicrobial susceptibility tests demonstrated that D-59 is susceptible to florfenicol, enrofloxacin, and neomycin sulfate. This study aimed to highlight the dangers of Staphylococcus sciuri infection during hybrid sturgeon culture and to provide recommendations for diagnosis and treatment.